2004
DOI: 10.1590/s0102-33062004000200018
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia comparada do pulvino, pecíolo e raque de Pterodon pubescens Benth. (Fabaceae - Faboideae)

Abstract: RESUMO -(Anatomia comparada do pulvino, pecíolo e raque de Pterodon pubescens Benth. (Fabaceae -Faboideae)). Em Pterodon pubescens, os pulvinos primário e secundário, órgãos responsáveis pelos movimentos foliares, apresentam peculiaridades estruturais em relação ao pecíolo e raque. Estas peculiaridades incluem cutícula mais espessa, córtex mais desenvolvido formado por células parenquimáticas de formas variáveis, sistema vascular em posição central, floema circundado por fibras septadas não lignificadas e medu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…The presence of secretory spaces is a condition shared by with some other members of the ADA clade (Angylocalyceae, Dipterygeae, Amburaneae, see Cardoso et al 2012;2013). In addition to the Dipterygeae clade (present study, Rodrigues & Machado 2004;Paiva et al 2008;Leite et al 2014), secretory spaces were reported in the leaves of Myrocarpus, Myrospermum and Myroxylon (Sartori & Tozzi 2002), which are part of the Amburaneae clade (Cardoso et al 2012;2013). Surprisingly, however, secretory spaces were not observed in leaves of Monopteryx auacu (FH Palermo unpubl.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…The presence of secretory spaces is a condition shared by with some other members of the ADA clade (Angylocalyceae, Dipterygeae, Amburaneae, see Cardoso et al 2012;2013). In addition to the Dipterygeae clade (present study, Rodrigues & Machado 2004;Paiva et al 2008;Leite et al 2014), secretory spaces were reported in the leaves of Myrocarpus, Myrospermum and Myroxylon (Sartori & Tozzi 2002), which are part of the Amburaneae clade (Cardoso et al 2012;2013). Surprisingly, however, secretory spaces were not observed in leaves of Monopteryx auacu (FH Palermo unpubl.…”
Section: Discussionsupporting
confidence: 43%
“…In this clade, the presence of secretory spaces in vegetative and reproductive organs is a well-known characteristic (Rodrigues & Machado 2004;Leite et al 2014), which (Rodrigues & Machado 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal secretory spaces of lipophilic compounds, including canals and cavities have been described in several organs of different species of Leguminosae (Langenheim et al 1978;Turner 1986;Lersten and Curtis 1996;Teixeira et al 2000;Teixeira and Gabrielli 2006;Marcati et al 2001;Rodrigues and Machado 2004;Paiva and Machado 2007;Paiva et al 2008). However, considering the abundance of legumes carrying secretory spaces, there are very few studies about them.…”
Section: Introductionmentioning
confidence: 99%
“…As características descritas para o pecíolo de P. laureola já foram relatadas para o pulvino de Pterodon pubescens Benth. (Fabaceae) por Rodrigues & Machado (2004), que as evidenciaram como responsáveis pelo movimento foliar. Os caracteres anatômicos inventariados indicam dois padrões estruturais para as folhas das espécies estudadas: mesomórficos e xeromórficos, ocorrentes tanto em restinga quanto cerrado (Tab.…”
Section: Resultsunclassified